The Effect Of Andaliman Fruit (Zanthoxylum Acanthopodium) Extract On Oxidative Stress In The Pancreas Of Rats (Ratus Norvegicus) Induced By D-Galactose - Felix Hartanto; Chrismis Novalinda Ginting; Linda Chiuman (Jurnal Teknologi Laboratorium)
ABSTRACT